2022
DOI: 10.7759/cureus.23490
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Pregnancy: Identification and Management at a Reference Center in Pakistan

Abstract: Objective: The study aimed to evaluate the causes of thrombocytopenia in pregnancy and its management along with the outcome in the COVID-19 era. Methods: Recruitment for this prospective, cross-sectional observational study of thrombocytopenia in pregnancy (platelet counts <100x10 9 /L) was done from January 2017 to August 2020 at the National Institute of Blood Diseases (NIBD) after taking the patients’ informed consent. Complete clinical and lab profile of patients was also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Among pregnant females, gestational thrombocytopenia, idiopathic thrombocytopenic purpura and pre-eclampsia are some of the most frequent causes behind gestational thrombocytopenia. 13,14 Some researchers have shown that gestational thrombocytopenia might increase the chances of excessive bleeding during or after the delivery especially among cases who undergo cesarean section or any other surgical procedure but these manifestations are more evident among cases of severe gestational thrombocytopenia. 15,16 We found the frequency of thrombocytopenia to be 10% among pregnant females attending the outpatient department for antenatal check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Among pregnant females, gestational thrombocytopenia, idiopathic thrombocytopenic purpura and pre-eclampsia are some of the most frequent causes behind gestational thrombocytopenia. 13,14 Some researchers have shown that gestational thrombocytopenia might increase the chances of excessive bleeding during or after the delivery especially among cases who undergo cesarean section or any other surgical procedure but these manifestations are more evident among cases of severe gestational thrombocytopenia. 15,16 We found the frequency of thrombocytopenia to be 10% among pregnant females attending the outpatient department for antenatal check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…This descriptive case series study was performed at the Obstetrics and Gynecology Unit III, Jinnah Hospital, Lahore, Pakistan, from April 2023 to September 2023. A sample size of 280 patients was calculated, taking the expected percentage of gestational thrombocytopenia in females presenting for delivery as 7% [ 1 ], with a confidence level of 95% and a margin of error of 3%. Sample selection was made employing a non-probability, consecutive sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…Platelet-related problems are more frequently discovered in women during pregnancy because screening is carried out as part of the initial clinic examination using automated blood counts [ 1 , 2 ]. Understanding the various causes of thrombocytopenia during pregnancy makes it easier to diagnose and treat thrombocytopenia in pregnant women [ 3 ].…”
Section: Introductionmentioning
confidence: 99%